Penetrating Neck Trauma Involving Zone I: Surgical Intervention and Outcomes - Lumintang, Nico; Paat, Rigel K.; Aruperes, Marturia I. (Universitas Sam Ratulangi, 2026)
Abstract: Penetrating neck injuries (PNI) are injuries that penetrate the platysma and represent a major cause of morbidity and mortality due to the vital structures confined in the neck area. They account for approximately 5–10 % of all trauma cases presenting to the emergency department. Depending on the depth of penetration and anatomy of trachea, the deeper the penetration, the bigger chance that tissues surrounding the trachea to be injured, causing complications including the lungs. We reported a male patient presented with respiratory distress approximately eight hours after sustaining a penetrating neck wound. Initially, he was fully conscious but had difficulty in breathing. Physical examination revealed low oxygen saturation, lagging movement of the right chest wall, dull right lungs percussion, absence of right vesicular breath sound, mild anemia, subcutaneous emphysema, and an anterior neck wound (3x2 cm) with no active bleeding. C-spine control, intubation and chest tube were performed. Chest auscultation identified persistent ronchi in the right lung. Imaging confirmed subcutaneous emphysema (C2-C7), right hemothorax, and tracheal rupture. Surgical intervention included wound explorationand tracheostomy. A vertical rupture involving the anterior tracheal rings (4–6) was identified and managed with a tracheal cannula. No posterior tracheal injury was found. Postoperatively, the patient showed improved airway patency with subsiding emphysema, though right lung expansion remained limited. In conclusion, this case highlights the proximity of vital structures poses challenges in surgical access, underscoring the need for meticulous airway management and postoperative monitoring. Keywords: pentrating neck trauma; tracheal rupture; subcutaneous emphysema; hemothorax